Changes in risk of extreme weather events in Europe. Issue 100 (October 2019) - Kron, Wolfgang; Löw, Petra; Kundzewicz, Zbigniew W.
Highlights: Weather disasters are a growing burden in Europe, because of increasing losses and costs of precautionary measures. Socio-economic, climatic and environmental changes drive the growing risk. The insurance industry can play a major role in the partnership for reduction of risk of weather extremes Abstract: Over the last decades, the damage caused by weather events has increased dramatically and ubiquitously. In Europe, weather catastrophes constitute a growing burden on national economies and insurance companies, not least because of the costs of precautionary measures. For a long time, the insurance sector has flagged that weather disasters are on the rise, both in terms of the number of occurrences and material damage caused. The main reasons for this are: increase in the number and area of settlements in exposed areas, the accumulation of ever more valuable and vulnerable assets in these areas, as well as the climate and environmental changes that have already taken place. This paper examines observed changes in risk of various categories of weather disasters in Europe, backed by statistical analyses of relevant, updated information originating from a valuable and quite unique source, Munich Re's NatCatSERVICE database, that is of considerable interest and value to the scientific community and beyond (e.g. in the reinsurance and insurance industries). The paper also calls for partnership in the reduction of risk of weather extremes and discusses the role of the insurance industry.